Visual and olfactory cues used in host location by the blister beetle Hycleus apicicornis (Coleoptera: Meloidae), a pest of Desmodium (Fabaceae) species - Kruger, Kerstin (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.